3D two-fingered caging for two types of objects: sufficient conditions and planning. (1st January 2013) - Makita, Satoshi; Okita, Kensuke; Maeda, Yusuke
Caging is a method to capture an object geometrically by robots. Position-controlled robots can make the object inescapable from the robot formation. Moreover less number of mobile robots or a robot hand with low degrees of freedom can constrain the object with considering concavity of the object. In this paper, we propose two types of caging: ring-type and waist-type, which both can be accomplished by a two-fingered hand. We derive sufficient conditions for caging of the two types and construct RRT-based motion planner for caging by a robotic arm/hand system. In motion planning, we find one of final configurations that satisfy the sufficient conditions and produce a path of robot configuration to the goal. With object recognition using AR picture markers, we can acquire geometrical information of objects and plan robot motion for caging. We show some experimental results of planning and execution of planned caging motion for four objects.